Design and control of an unmanned surface vehicle for environmental monitoring applications (2017)
Unmanned Surface Vehicles (USV) have been used in a wide range of applications, in particular in environmental monitoring. In this work we propose the design and control of an USV which is intended to be used for monitoring environmental variables of the main inlet waters located in Cartagena de Indias, Colombia, such as Chambacu, Cabrero and San Lazaro. The paper shows the results obtained in the naval design, focused on the hull design, and the control strategy for unmanned navigability which is tested in simulation. © 2016 IEEE.